Mapping Global Publication Trends on Digital Social Work: A Systematic Literature Review - Khoirul Anam; Salahudin Salahudin (Journal of Social Development Studies, 2026)
Digital Social Work improves the efficiency of social services through the use of digital technology in social work practices. This study aims to identify global publication trends and conceptual developments in Digital Social Work through a Systematic Literature Review (SLR). A total of 1,732 articles on digital social work indexed in the Scopus database were analyzed through a review using Vosviewer. The results reveal several dominant themes, namely social media, technology, and human-centered approaches, which form the core of Digital Social Work research. The findings also indicate that digital transformation brings both opportunities and challenges, including improved service accessibility and efficiency, as well as issues related to data protection, ethics, and digital inequality. Furthermore, the study identifies a shift in research trends from basic technological adoption toward more complex themes such as sustainability, social policy, and well-being. These results contribute to understanding the development of Digital Social Work as a dynamic and multidisciplinary field. However, this study is limited to the Scopus database and a specific time frame. Future research should incorporate additional databases, such as the Web od Science and extend the analysis period to provide a more comprehensive perspective.